An Empirical Assessment of Local Food Practices as Drivers of Sustainable Tourism Innovation in Madhya Pradesh’s Post-Pandemic Landscape - Shakti Prathaban; Ram Krishna Patel (AG Volumes, 2026)
Such research explores the role of local culinary traditions as valuable triggers of new kinds of sustainable tourism in the region within the environment of Madhya Pradesh post-pandemic. Culinary tourism has indeed become an effective tool in revitalizing the local tourist ecosystems as the travel industry is experiencing a paradigm shift towards authenticity, neighborhood integration, and responsibility to the environment. To create conditions under which demographical aspects can be evaluated in the context of local food involvement and its perceived connection with sustainable tourism, the study was conducted with structured questionnaires being issued to 98 respondents. The findings indicate that the youth and students associate greatly with participatory cooking classes and farm-to-table events, which are immersive activities. The rate at which foods were explored and the perceived sustainability and likelihood of a recommendation were proved to be significantly correlated. Even though accessibility and sanitation were reported to be big barriers, the majority of the respondents remained highly in favor of food-based tourist experiences. The study sheds light on the possibility that culinary innovation can act as one of the sustainable development strategies, as well as a branding tool. It is also informative enough to make local business proprietors, legislators, and tourist planners reconsider such marketing strategies as those based on the culinary heritage. Finally, the research demonstrates that local food can transform local tourism into a sustainable and culturally immersive one when intervened into the tourist value chain ingeniously.